Avian species “at risk” in the cloud forests of five IBAs of the Sierra Madre Oriental, Mexico - Pablo Caballero-Cruz; Guillermo Vargas-Noguez; Raúl Ortiz-Pulido (Huitzil, 2020)
One hundred twenty-five endangered or endemic bird species inhabit the cloud forests of Mexico. In a time of loss of biodiversity and reduction of cloud forest it is important to determine which species inhabit this ecosystem. Unfortunately, the cloud forests located in the Sierra Madre Oriental, Mexico, have been little studied, lacking even a basic inventory of the avian species present. In order to fill this lack of information, here we report observations  of endangered and/or endemic bird species documented in 2016 in five Important Bird Areas (Sierra Gorda, Tlanchinol, Huayacocotla, Cuetzalan y Río Metlac) located in four Mexican states (Querétaro, Hidalgo, Veracruz y Puebla). We recorded 60 (48%) of the 125 bird species considered at risk, 29 are endangered at the national level and 34 show some kind of endemism. Six species are protected globally (Dendrortyx barbatus, Ara militaris, Contopus cooperi, Ridgwayia pinicola, Setophaga chrysoparia y Passerina ciris).